Optimalisasi peran & fungsi manajemen kepala ruangan dalam supervisi dokumentasi asuhan keperawatan di rumah sakit x Jakarta - Teresa Teresa; Tuti Afrianti; Tini Suminarti (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
The role of a head nurse in optimizing of management function in supervision of nursing care documentation at X hospital in JakartaBackground: Nursing documentation is important thing that is indicator quality of care. Since the nursing documentation is still a poor quality, it requires a supervision by the head nurse.Purpose: The head of nursing is responsible for the direction, organization and strategic planning collaborate with nursing staffs in ensuring the quality of nursing care to achieve accurate, effective and efficient documentation and to complete supervision.Method: A pilot project using questionnaire and observation methods was conducted at difference times on two hospital units in Jakarta.Results: The descriptive analysis results showed that among 18 nurses, 4 nurses believed that nursing documentation is an important, effective and clear way to ease their job. Hence, supervision is continuity needed to support the improvement of health care quality. The innovative projects will be applied in health care.Conclusion: Nursing documentation must show continuity and quality of care nursing under the control and supervision of the head nurse and EMR is used as the instrument for documentation.Keywords : The role; Head nurse; Management; Supervision; Nursing care; DocumentationPendahuluan: Dokumentasi asuhan keperawatan adalah hal yang penting karena menjadi indikator kualitas perawatan. Penerapan dokumentasi asuhan keperawatan saat ini belum optimal sehingga membutuhkan arahan dan supervisi dari Kepala Ruang/Kepala Unit.Tujuan: Tercapainya supervisi dan keberhasilan pelaksanaan dokumentasi asuhan keperawatan yang komprehensif, berkesinambungan, efektif dan efisien.Metode: Metode pilot project di salah satu Rumah Sakit di Jakarta dengan pengambilan data melalui observasi dan kuestioner. Instrumen diujikan pada dua ruangan dalam waktu yang berbeda.Hasil: Analisis deskripsi pada sejumlah 18 perawat, 4 orang menyatakan bermanfaat, penting dan mudah dalam penerapannya. Supervisi dilakukan untuk memberikan support terhadap kelangsungan pendokumentasian asuhan keperawatan yang berkesinambungan. Proyek inovasi akan ditindaklanjuti dan diaplikasikan dalam program kerja bidang pelayanan keperawatan.Simpulan: Asuhan keperawatan yang berkualitas memerlukan adanya supervisi. Sarannya penggunaan Instrumen Supervise Dokumentasi Asuhan Keperawatan akan disesuaikan dengan penggunaan pencatatan asuhan keperawatan Elektronic Medical Record/EMR